2022
DOI: 10.1021/acsnano.2c02281
|View full text |Cite
|
Sign up to set email alerts
|

The Overlooked Photochemistry of Iodine in Aqueous Suspensions of Fullerene Derivatives

Abstract: Fullerene’s low water solubility was a serious challenge to researchers aiming to harness their excellent photochemical properties for aqueous applications. Cationic functionalization of the fullerene cage provided the most effective approach to increase water solubility, but common synthesis practices inadvertently complicated the photochemistry of these systems by introducing iodide as a counterion. This problem was overlooked until recent work noted a potentiation effect which occurred when photosensitizers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…3,5-Dimethyl-1 H -pyrazole (DMPZ), as a probe for iodine radicals (I • , I 2 •– ), was likely to form I – DMPZ under light irradiation through the addition reaction . The mixture solution of OG (0.15 mM) and KI (250 mM) with DMPZ (10 μM) was under BL irradiation for 0, 30, 60, and 90 min (420 nm, 210 mW/cm 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…3,5-Dimethyl-1 H -pyrazole (DMPZ), as a probe for iodine radicals (I • , I 2 •– ), was likely to form I – DMPZ under light irradiation through the addition reaction . The mixture solution of OG (0.15 mM) and KI (250 mM) with DMPZ (10 μM) was under BL irradiation for 0, 30, 60, and 90 min (420 nm, 210 mW/cm 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…As a result, it is only soluble in benzene, toluene, and other aromatic solvents [21]. It has been reported that underived fullerene C 60 has low solubility in polar solvents and a solubility of only 1.3 × 10 − 11 g/L in water at 17°C [22]; these properties limit its application in the biomedical eld. Therefore, chemical modi cation methods based on the amino, carboxyl, and hydroxyl groups are often used to modify its physical and chemical properties and improve its bioavailability.…”
Section: Introductionmentioning
confidence: 99%